2016
DOI: 10.1016/j.celrep.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

The SIRT2 Deacetylase Stabilizes Slug to Control Malignancy of Basal-like Breast Cancer

Abstract: Summary Overabundance of Slug protein is common in human cancer and represents an important determinant underlying the aggressiveness of basal-like breast cancer (BLBC). Despite its importance, this transcription factor is rarely mutated in BLBC, and the mechanism of its deregulation in cancer remains unknown. Here we report that Slug undergoes acetylation-dependent protein degradation and identify the deacetylase SIRT2 as a key mediator of this post-translational mechanism. SIRT2 inhibition rapidly destabiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
77
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 71 publications
7
77
1
Order By: Relevance
“…However, the detailed regulatory mechanisms for these two molecules in different tissues remain to be investigated. Slug reportedly undergoes acetylation-dependent protein degradation, and the deacetylase SIRT2 was identified as a key mediator of this posttranslational mechanism [53]. These findings are in agreement with the notion that Slug is a labile protein that is subjected to delicate regulation by multiple signaling pathways to control its ubiquitylation and degradation.…”
Section: Discussionsupporting
confidence: 76%
“…However, the detailed regulatory mechanisms for these two molecules in different tissues remain to be investigated. Slug reportedly undergoes acetylation-dependent protein degradation, and the deacetylase SIRT2 was identified as a key mediator of this posttranslational mechanism [53]. These findings are in agreement with the notion that Slug is a labile protein that is subjected to delicate regulation by multiple signaling pathways to control its ubiquitylation and degradation.…”
Section: Discussionsupporting
confidence: 76%
“…There are seven sirtuin members in mammals, sirtuin 1–7 (SIRT1–7), and these exhibit diverse functions, including transcriptional silencing, metabolic regulation, and apoptosis. SIRT2 is localized to both the nucleus and the cytoplasm and deacetylates α‐tubulin, FOXO1, FOXO3a, p300, Lys16 of histone H4, Slug, CDH1, CDC20, and p53 . SIRT2 also deacetylates the transcriptional repressor Slug to prevent its degradation and thereby controls malignancy of basal‐like breast cancer .…”
Section: Introductionmentioning
confidence: 99%
“…SIRT2 is localized to both the nucleus and the cytoplasm [8][9][10][11] and deacetylates a-tubulin, FOXO1, FOXO3a, p300, Lys16 of histone H4, Slug, CDH1, CDC20, and p53 [8][9][10][11][12][13]. SIRT2 also deacetylates the transcriptional repressor Slug to prevent its degradation and thereby controls malignancy of basal-like breast cancer [11]. Furthermore, a SIRT2-specific inhibitor, a thiomyristoyl lysine compound, promotes c-Myc ubiquitination and degradation and exhibits broad anticancer activity [14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that SIRT2, as a strong deacetylase [23][24][25][26], is highly expressed in the brain and is markedly associated with aging [27,28]; additionally, SIRT2 was evaluated in the brains of PD patients, suggesting a potential role in PD development [29]. It has been confirmed that selective inhibitors of SIRT2 can protect against α-syn-mediated toxicity and dopaminergic cell death, both in vitro and in a Drosophila model of PD [19].…”
Section: Discussionmentioning
confidence: 94%